Elasticidade de oferta agropecuária agregada de área selecionada do sul do Brasil - Brandt, Sérgio Alberto; Fagundes de Sousa, Antônio; Dias Teixeira, Teotônio; Martins Rezende, Alberto; Tonini, Enio (Revista Ceres, 2025)
The analysis of aggregate supply relationships might play a significant role in providing a basis for price policy favoring agricultural producers. The objectives of the present supply study may be summarized as follows: a) to improve understanding of the mechanism of aggregate production response, b) to improve predictions of aggregate production changes, c) to improve the effecti- veness of policies affecting aggregate supply, and d) to improve the understanding of the impact of programs of imports, exports, taxation, and incentives on the aggregate agricultural production.